Caregiver burden and its associated factors among family caregivers of persons with dementia in Shanghai, China: a cross-sectional study. Issue 5 (24th May 2022) - Liu, Zhijian; Sun, Wenjing; Chen, Honglin; Zhuang, Jianhua; Wu, Bei; Xu, Hanzhang; Li, Peng; Chen, Xiaohan; Li, Juan; Yin, You
Abstract : Objective: To assess the level of caregiver burden and factors associated with it among family caregivers of persons with dementia (PWD) living in communities of Shanghai, China. Design: Cross-sectional study. Setting: Communities in Hongkou District of Shanghai, China. Participants: A random sample of 109 older adults with dementia and their primary family caregivers. Main outcome measure: Caregiver burden measured by the Caregiver Burden Inventory (CBI), and the Caregivers' depressive symptom measured by the simplified Chinese version of Self-rating Depression Scale was the outcome variable of the study. The independent variables, including the cognitive function (measured by Montreal Cognitive Assessment (MoCA), sleep quality assessed by the Pittsburgh Sleep Quality Index, abilities of daily life assessed by the Activities of Daily Living Scale, and behavioural and psychological symptoms assessed by the Neuropsychiatric Inventory of PWDs, the community service utilisation (measured by the Community Service Utilisation Measurement), perceived social support (assessed by three questions), positive aspects of caregiving (PAC) (assessed by the PAC) of dementia caregivers, were analysed. Multivariate linear regression was employed to determine the factors related to caregiver burden. Results: The average level of CBI was 65.92±16.74. The score of MoCA, PAC and perceived social support of caregivers were negatively associated with caregiver burden (β=−0.84, p<0.001, β=−3.61, p=0.03 and β=−1.22, p=0.001, respectively). Community service utilisation was positively associated (β=3.46, p<0.001) with caregiver burden. Perceived social support by the caregiver moderated the relationship between caregiver burden and caregivers' depression symptoms. Conclusion: Dementia caregivers experienced a high level of caregiver burden. The cognitive function of PWD, PAC, social support and community service utilisation were factors associated with caregiver burden. Strengthening social support, providing more high-quality home care services, promoting PAC are imperative to reduce caregiver burden.